Th1/Th2 Cells and Associated Cytokines in Acute Hepatitis E and Related Acute Liver Failure - Jian Wu; Yurong Guo; Xuan Lu; Fen Huang; Feifei Lv; Daqiao Wei; Anquan Shang; Jinfeng Yang; Qiaoling Pan; Bin Jiang; Jiong Yu; Hongcui Cao; et al. (Journal of Immunology Research)
Background and Aims. The involvement of cellular immunity in the development of hepatitis E virus (HEV) infection is rare. We aimed to study the roles of viral load and Th cell responses in acute hepatitis E (AHE) and HEV-related acute liver failure (HEV-ALF). Methods. We evaluated viral load and Th1/Th2 cytokine levels in 34 patients with HEV infection, including 17 each with AHE or HEV-ALF. Seventeen healthy controls (HCs) were also included who were negative for anti-HEV IgM and IgG. Results. There was no significant difference in viral load and HEV RNA in the AHE and HEV-ALF groups (both P>0.05). The Th lymphocyte levels (CD3+, CD4+) in the AHE and HEV-ALF groups were significantly higher than those in the HC group (both P<0.05), but there was no significant difference between the AHE and HEV-ALF groups (P>0.05). Both IFN-γ and IL-10 showed gradual upward trend from the HC group to the AHE (both P<0.01), but IFN-γ showed a sharp downward trend from the AHE group to the HEV-ALF group (P<0.01) and IL-4 showed gradual upward trend from the AHE group to the HEV-ALF group (P<0.01).There was no significant difference in Th1 and Th2 cytokines between the HEV RNA(+) group and HEV RNA(-) group (all P>0.05). Th2 bias was observed from the AHE (ratio=58.65) to HEV-ALF (ratio=1.20) groups. The level of IFN-γ was associated with the outcome of HEV-ALF patients. Conclusions. HEV viral load was not associated with aggravation of AHE, and the HEV-ALF patients showed significant Th2 bias, which may be involved in the aggravation of AHE.